Challenging the Future with Education - Nugroho, Kuncoro Asih (Journal of English and Education (JEE), 2007)
The paper discusses the possible ways' of improving the quality of education in Indonesia in the future. It starts with the background describing die reality of the education nowadays and the need of making changing in any aspect of education.To yield better products of education, there must be improvements in the process of education, in which each components of education system should interact one another. Besides, the purpose of education should be clear and inclusive which does not only concern in the cognitive side but also in affective and psychomotor sides. After setting the purpose of education there must be a change in education paradigm as well. We have to see that education is a means to make students mature in their life. To generate change, innovations must be made by any parties of education process. Especially teachers should always innovate their teaching method so that the result of their teaching process will be maximum. Last but not least, education should ensure the output and the outcome. When the aspects above mentioned are well carried out, education will not only yield better output, which has good grades or marks, but it will also yield better outcome which will not find difficulties in getting the first job.